Freeze-thaw resistance of Class F fly ash-based geopolymer concrete. (20th October 2019) - Zhao, Renda; Yuan, Yuan; Cheng, Zhengqing; Wen, Tian; Li, Jian; Li, Fuhai; Ma, Zhongguo John
Highlights: Compressive strength was improved by elevating curing temperature and adding slag. High temperature curing has a slight improvement on the freeze-thaw resistance. The freeze-thaw resistance increases with the increase of slag content. An inflection point of freeze-thaw resistance of GPC-50. Abstract: A set of Class F fly ash-based geopolymer concrete with slag gradient, namely, GPC-10 (10% slag content), GPC-30 (30% slag content) and GPC-50 (50% slag content), was prepared to study its freeze-thaw resistance. GPC-10 was wrapped in aluminum foil and cured at 80 °C for 24 h to accelerate strength development. The others were cured under standard conditions (20 ± 2 °C, relative humidity ≥95%). Rapid freeze-thaw cycle testing was carried out according to ASTM C666, and an ordinary Portland cement concrete (OPCC) sample was used as the control. The freeze-thaw resistance was evaluated by mass loss, relative dynamic elasticity modulus and compressive strength loss. In addition, the microstructure and mineralogy were characterized using scanning electron microscopy (SEM), mercury intrusion porosimetry (MIP), energy dispersive X-ray spectrosocpy (EDS) and X-ray diffraction (XRD). The results show that GPC-10 is damaged after five freeze-thaw cycles, although high temperature curing improves its freeze-thaw resistance. GPC-30 is damaged in 50 freeze-thaw cycles, while GPC-50 can withstand 225 freeze-thaw cycles, which is comparable to the freeze-thaw resistance of the OPCC. Also, 125 freeze-thaw cycles marks an inflection point for the freeze-thaw resistance of GPC-50, which is verified by the SEM and MIP results. The effect of adding slag on the enhanced freeze-thaw resistance was analyzed by EDS and XRD.